Tatak Pilipino [episode no. 26] % Tatak Pilipino episode no. 21]. ([Quezon City ABS-CBN, 1991)
A uniquely Pilipino way and style.
[Episode no. 20 (55 min.). Historical calendar events of April 6-13 (5 min.) -- 100 Most significant Filipinos of the twentieth century-25 (15 min.) -- Pilipino terms in International English dictionary (5 min.) -- Foreigners speaking Pilipino (15 min.) -- Gymnastics (10 min.) -- Pacita Abad : Filipino painter (15 min.) -- [Episode no. 21] (55 min.). Nganga (15 min.) -- 100 Most significant Filipinos of the twentith century-20 (15 min.) -- Grotto in San Jose Del Monte, Bulacan (15 min.) --Tallest buildings (5 min.) -- Historical calendar events of April 14-17 (5 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Mary, Blessed Virgin, Saint -- Shrines; Gymnasts -- Philippines; Pilipino language -- Study and teaching -- Foreign speakers; Filipino language; Filipinos -- Biography; Buildings; Mastication; Philippines -- History